Estudio de factibilidad para la implementación del protocolo de red de capa de transporte dns-over-quic (doq) en la universidad técnica de Babahoyo - Caicedo Paredes, Jefferson Jesús (2022)
DNS-over-QUIC (DoQ) is a protocol that was officially standardised in 2021, which serves to protect user security and privacy while adding speed when performing DNS domain name queries on the internet. In relation to the benefits of the aforementioned protocol, the objective of this case study is to determine the feasibility of implementing the DNS-over-QUIC (DoQ) transport layer network protocol at the Technical University of Babahoyo. The methodology used for this project was a descriptive research, through the techniques used, a survey was conducted to assess the knowledge of people intrinsically related to the academic institution of higher level, being the same the main beneficiaries in the implementation of this protocol. Additionally, an interview was conducted with the director of the systems department to gather information about the general structure of the university network, information that will help the development of the respective case study.